Sosialisasi Hukum tentang Kejahatan Siber - Budi Handayani; Tuti Herningtyas; Haniyah Haniyah; Roidatus Shofiyah; Atmari Atmari (ARDHI : Jurnal Pengabdian Dalam Negri, 2023)
The development of information and communication technology has significantly influenced people’s lives, particularly in the use of digital media and social media. However, this development has also led to various forms of cybercrime, such as online fraud, personal data theft, the spread of hoaxes, and social media account hacking. The low level of digital literacy and public legal awareness has become one of the factors increasing the risk of cybercrime. This community service activity aimed to improve public awareness and legal understanding regarding the dangers of cybercrime through legal socialization activities. The method used in this activity was a socialization method with educational and participatory approaches through lectures, interactive discussions, question-and-answer sessions, and case simulations. The results of the activity showed an improvement in public understanding of the forms of cybercrime, legal consequences, and preventive measures for safe and responsible digital media use. In addition, this activity encouraged the emergence of public awareness to use social media wisely and protect personal data security. Therefore, legal socialization regarding cybercrime can serve as a preventive effort in building a law-aware society with good digital literacy.